2005
DOI: 10.3727/000000005783983232
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Islets in Rough Surface, Hydroxymethylated Polysulfone Capillaries Stimulates VEGF Release and Promotes Vascularization after Transplantation

Abstract: The transplantation of encapsulated islets of Langerhans is one approach to treat type 1 diabetes without the need of lifelong immunosuppression. Capillaries have been used for macroencapsulation because they have a favorable surface-to-volume ratio and because they can be refilled. It is unclear at present whether the outer surface of such capillaries should be smooth to prevent, or rough to promote, cell adhesions. In this study we tested a new capillary made of modified polysulfone (MWCO: 50 kDa) with a rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Second, enlargement of the apical foramen is necessary to promote vascularizaton and to maintain initial cell viability via nutrient diffusion. Related to this point, cells must have an available supply of oxygen; therefore, it is likely that cells in the (122)(123)(124)(125)(126).…”
Section: Root Canal Revascularization Via Blood Clottingmentioning
confidence: 99%
“…Second, enlargement of the apical foramen is necessary to promote vascularizaton and to maintain initial cell viability via nutrient diffusion. Related to this point, cells must have an available supply of oxygen; therefore, it is likely that cells in the (122)(123)(124)(125)(126).…”
Section: Root Canal Revascularization Via Blood Clottingmentioning
confidence: 99%
“…This effect was even more pronounced when islets are encapsulated (21)(22)(23)(24). Experimental approaches to overcome this problem include the generation of very small capsules (25), use of hypoxia-resistant islet cells (26), stimulation of blood vessel growth around implanted devices (27,28), increased oxygen permeability of the encapsulating material (29,30), use of To whom correspondence should be addressed. E-mail: andrew.schally@va.gov.…”
mentioning
confidence: 99%
“…Lembert et al [39,40] developed hydroxy-methylated PSU "macroencapsulated" islets which showed good insulin releasing function similar to naked islets while blocking endogenous retrovirus infection. Transplantation of their device also achieved normoglycemia in diabetic rats for over 1 mo [41] . Polyvinyl alcohol (PVA) also has been used as a material for encapsulated islets.…”
Section: Resultsmentioning
confidence: 99%
“…Alginate [36] Microcapsule Porcine and bovine to rat Achieving normoglycemia for 9 mo Polysulphone [41] Macrocapsule Porcine to rat Normoglycemia over 1 mo Polyvinyl alcoho [8] Macrocapsule Rat to mouse Normoglycemia for 30 d Low molecular weight dextran sulfate [47] Microcapsule In vitro assay Inhibition of complement Figure 1 Scheme of the mechanism for encapsulated islets. Immune isolation can be achieved by covering islets with semi-permeable membranes consisting of high polymer.…”
Section: Resultsmentioning
confidence: 99%